Peripheral T3 signaling is the target of pesticides in zebrafish larvae and adult liver. Issue 1 (October 2020) - Colella, Marco; Nittoli, Valeria; Porciello, Alfonsina; Porreca, Immacolata; Reale, Carla; Russo, Filomena; Russo, Nicola Antonino; Roberto, Luca; Albano, Francesco; De Felice, Mario; Mallardo, Massimo; Ambrosino, Concetta
Abstract : The intra-tissue levels of thyroid hormones (THs) regulate organ functions. Environmental factors can impair these levels by damaging the thyroid gland and/or peripheral TH metabolism. We investigated the effects of embryonic and/or long-life exposure to low-dose pesticides, ethylene thiourea (ETU), chlorpyrifos (CPF) and both combined on intra-tissue T4 /T3 metabolism/signaling in zebrafish at different life stages. Hypothyroidism was evident in exposed larvae that showed reduced number of follicles and induced tshb mRNAs. Despite that, we found an increase in free T4 (fT4) and free T3 (fT3) levels/signaling that was confirmed by transcriptional regulation of TH metabolic enzymes (deiodinases) and T3-regulated mRNAs ( cpt1, igfbp1a ). Second-generation larvae showed that thyroid and TH signaling was affected even when not directly exposed, suggesting the role of parental exposure. In adult zebrafish, we found that sex-dependent damage of hepatic T3 level/signaling was associated with liver steatosis, which was more pronounced in females, with sex-dependent alteration of transcripts codifying the key enzymes involved in ' de novo lipogenesis' and β-oxidation. We found impaired activation of liver T3 and PPARα/Foxo3a pathways whose deregulation was already involved in mammalian liver steatosis. The data emphasizes that the intra-tissue imbalance of the T3 level is due to thyroid endocrine disruptors (THDC) and suggests that the effect of a slight modification in T3 signaling might be amplified by its direct regulation or crosstalk with PPARα/Foxo3a pathways. Because T3 levels define the hypothyroid/hyperthyroid status of each organ, our findings might explain the pleiotropic and site-dependent effects of pesticides.